The Impact of Management Factors on Lecturer Professionalism and Teaching Quality Performance - Siti Saodah Susanti; Hery Saparudin; Lia Saniah (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study investigates the influence of management factors—Total Quality Management (TQM), pedagogical competence, and empowerment management—on the professionalism and teaching performance quality of lecturers. A quantitative approach with a correlational design was employed. The total population, consisting of fewer than 100 lecturers, was selected using total sampling. Data collection utilized a Likert-scale questionnaire (1-5), and analysis was conducted using Structural Equation Modeling (SEM) via SmartPLS. Findings reveal that TQM does not significantly impact the quality of teaching performance but has a significant positive effect on lecturer professionalism. Conversely, pedagogical competence significantly influences teaching performance quality but does not affect professionalism. Empowerment management shows no significant relationship with teaching performance quality, yet it significantly impacts lecturer professionalism. While lecturer professionalism positively affects teaching performance, TQM, pedagogical competence, and empowerment management, when mediated through professionalism, do not exhibit a significant effect on performance quality. These results suggest the limited effectiveness is due to suboptimal implementation, insufficient management support, and external factors such as creativity, teaching experience, and work environment. The study underscores the need for improved TQM practices aligned with instructional goals, targeted pedagogical training, and more structured empowerment initiatives to enhance lecturer performance. Future research should explore additional factors, including creativity, teaching experience, and organizational culture, to gain a comprehensive understanding of determinants influencing teaching performance quality.